Content marketing: A new form of postmodern communication in tourism - Radenković-Šošić Bojana (University Educons, Faculty of Sports and Tourism, Novi Sad, 2013)
In the context of a changing marketing paradigm and the transition from the modern to the postmodern marketing concept, the communication between consumers and organizations has changed. With the development of interactive communication, the consumers are beginning to have a greater influence on the consumer process. Internet, as a dominant communication channel, has had an impact on the high degree of information availability, as well as on the proliferation of well-informed consumers and their impact on the environment. This paper examines the theoretical base and the main characteristics of postmodern marketing and its concrete implications on the tourism market. Considering the global trends of contemporary marketing, the purpose of this paper is to identify the general tendencies in marketing in order to associate them with basic postmodern theories of French philosophers and to indicate new forms of marketing communication in tourism. The paper analyses elementary features of content marketing and its present professional and academic research results.